Seismic Performance of Staircases in the 3D Analysis of RC Building - Omnia Hussien Ahmed; Abdel-Rahman Hazem; Ashraf Adel Shawky (Civil Engineering Journal, 2021)
Stairs play an important role as an escape way and are considered a source of safety in the building during an earthquake. Neglecting the stairs in the 3D analysis model is the main cause of the stairs' failure during the earthquake. Although the previous researchers had focused on the behavior of stairs when changing single variables such as height, location, and layout under seismic loads, no detailed investigation that gathers these variables together was considered. This research studies the effects of changing the number of storeys for a building subjected to an earthquake when considering and neglecting stairs in the 3D analysis with and without shear walls. The effect of the volume and location of the shear wall has been considered through conducting computational analysis using ETABS software to help the structural engineer choose the proper system of stairs and shear walls. Neglecting the staircase in the 3D analysis affects the structure's performance, which leads to ignoring many stresses transferred to the stairs, causing several damages to the stairs during an earthquake. For the existing building without a shear wall, considering the staircases in the analysis improves the performance of the structure under seismic loads. Doi: 10.28991/CEJ-SP2021-07-08 Full Text: PDF